Enhancing Students’ Understanding of Qur’anic Text Comprehension through the Think-Pair-Share Strategy: Evidence from Madrasah Tsanawiyah - Sopian, Agus (LPTK UIN Syekh Wasil Kediri, 2025)
This classroom action research examines the effectiveness of the Think-Pair-Share strategy, adapted into the TPS-ADR model (Quranic Verse, Discussion, Reflection), in improving students’ comprehension of the Quranic verse. Al-Mujadilah:11 and learning outcomes. The study involved 25 Grade IX students at MTs Persis Cikalongkulon and used the Kemmis and McTaggart model in two cycles. Data were collected through achievement tests, participant observation using the ORIVI rubric, and interviews. The results indicate consistent improvement in students’ learning achievement. In the pre-cycle stage, the average score was 64.8, with only 32% of students achieving mastery. After implementing TPS-ADR in Cycle I, the average score increased to 70.2, and mastery reached 60%. Further improvement was observed in Cycle II, with the average score rising to 83.6 and classical mastery increasing to 92%. Classroom observations also showed better student engagement and collaboration during the learning process. It can be concluded that the TPS-ADR model is effective in enhancing students’ comprehension of analytical Quranic verses and improving learning outcomes, particularly in pesantren-based madrasah contexts. This strategy can be recommended as an innovative instructional approach for Quranic learning that integrates collaborative discussion and reflective activities.